An assessment of the sulfur dioxide concentration and its human health effects in Naga, Cebu, Philippines - Roña, Ramon G. (University of the Philippines in the Visayas-Cebu College, 2005)
Naga is an industrial town in the southern part of Cebu Province. Its hosts a cement manufacturing firm and thermal power plants that utilize coal, bunker and diesel fuels to generate electricity. This study measured the ambient SO2 concentration and its related health effects to Naga residents and neighboring areas from September 2004 to January 2005. Fifteen barangays were chosen as study sites. Ambient SO2 concentration was measured using Passive Sampling Method. The Calpuff Modeling System was applied to simulate the present concentration level of SO2. Household surveys were conducted to assess the socio-economic and health profile of the local residents. Results showed that Cogon has the highest mean SO2 concentration of 3.2 ppb (8.5ug/m3). Bairan with 3.0 ppb (7.9 ug/m3) and Cantao-an with 2.8 ppb (7.5 ug/m3).The results of the model simulation showed no correlation with the observed data which could be attributed to the use of inappropriate emission, topography, and meteorological data. Furthermore, the results obtained from the study sites showed that the trend of the present SO2 concentration is way below the standard 70 pbb(180 ug/m3) of the Philippine Clean Air Act of 1999. The results imply that Naga and its neighboring areas were not yet heavily polluted with SO2 pollutants. Likewise, the result of the study showed that there were no noticeable trend of high incidents of respiratory, skin and eye ailments that maybe caused by SO2 pollutants.